DIATOMS AS CARDINAL KEY TO DROWNING CASE STUDIES (Journal of Forensic Medicine & Toxicology, 2015)
In the present report, 38 human drowning case studies from Haryana (India) were examined and solved by using “diatom test” in Forensic Science Laboratory Madhuban, Karnal (Haryana). After medico-legal examination, crime exhibits were sent to the laboratory along with the samples of water from which the dead bodies were recovered. Exhibits were treated with acid digestion, centrifugation and later on analyzed under the microscope for the presence of diatoms if any. Out of 38 cases, 34 cases were found to be positive for the diatom test as the crime exhibits (sternum, clavicle, liver, lungs, spleen, kidney, intestine, heart and putrefied viscera) had the same diatom types as were present in water samples from the drowning sites of the respective cases.
Keywords: Diatom test; microscope; crime exhibits; drowning sites